Pathogenic function of bystander-activated memory-like CD4+ T cells in autoimmune encephalomyelitis - Hong-Gyun Lee (Nature Portfolio, 2019)
T cells express specific T cell receptors (TCR) to recognise antigens and initiate adaptive immune responses. Here the authors show, in a mouse model of autoimmune encephalomyelitis, that memory-like CD4 T cells expressing unrelated TCR can also infiltrate the spinal cord and contribute to autoimmunity.